Cryptanalysis of A New Method of Cryptography using Laplace Transform Hyperbolic Functions - Gencoglu, M. Tuncay (Rgn Publ, 2017)
Although Laplace Transform is a good application field in the design of cryptosystems, many encryption algorithm proposals become unsatisfactory for secure communication since cryptanalysis studies are not sufficient. One of the important factors resulting in poor proposals is the fact that security analysis of the proposed encryption algorithms is performed with only statistical tests and experimental results. In this study, a general attack scenario was given in order to conduct security analyses of Laplace Transform based cryptosystems. The application of proposed general attack scenario was shown on recently proposed Laplace Transform based encryption scheme.
Keywords: Laplace transform; Cryptography; Cryptanalysis; A general attack scenario